Integrating Localized Approaches in Quality Assurance Frameworks: A Case Study of Rural Education Systems - John Mith; Mara Zalez (Yayasan Azhar Amanaa Yogyakarta, 2025)
This study explores the integration of localized Quality Assurance (QA) practices within rural education systems, focusing on their impact on educational outcomes and the perceptions of stakeholders, including school leaders, teachers, parents, and local authorities. Employing a qualitative case study approach, the research investigates how context-specific QA practices, adapted to the unique needs of rural schools, influence student engagement, academic performance, and overall school effectiveness. Data were collected through semi-structured interviews, focus groups, document analysis, and field observations across several rural schools in [insert region]. The findings suggest that localized QA practices, such as tailoring curricula to local cultural, social, and economic contexts, significantly improve student participation and learning outcomes. However, challenges such as limited resources, teacher training, and infrastructure were identified as barriers to the successful implementation of these practices. Despite these challenges, the integration of localized QA approaches was widely supported by stakeholders, who noted improved educational engagement and a stronger connection between students and their learning material. The study concludes that adapting QA frameworks to local contexts can enhance the relevance and effectiveness of education in rural settings, with policy recommendations for greater resource allocation, teacher professional development, and ongoing evaluation of localized approaches